Новая физика за пределами стандартной модели - Мaлютa, Ю.M.; Обиход, Т.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Spectra of graviton KK-partners and vector boson KK-partners are compared with computer simulation data given in a CMS Technical Design Report.